2019
DOI: 10.1021/acs.jafc.9b04274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cinnamaldehyde as Most Effective Fatty Acid Uptake Reducing Cinnamon-Derived Compound in Differentiated Caco-2 Cells Compared to Its Structural Analogues Cinnamyl Alcohol, Cinnamic Acid, and Cinnamyl Isobutyrate

Abstract: Naturally occurring cinnamon compounds such as cinnamaldehyde (CAL) and structurally related constituents have been associated with antiobesity activities, although studies regarding the impact on intestinal fatty acid uptake are scarce. Here, we demonstrate the effects of CAL and structural analogues cinnamyl alcohol (CALC), cinnamic acid (CAC), and cinnamyl isobutyrate on mechanisms regulating intestinal fatty acid uptake in differentiated Caco-2 cells. CAL, CALC, and CAC (3000 μM) were found to decrease fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 67 publications
(167 reference statements)
3
13
0
Order By: Relevance
“…34 Consistently, marked alcohol-induced hepatic lipid/triglyceride accumulation was observed in the EtOH group, indicated by Oil red O staining and elevated liver TC and TG contents. In agreement with previous studies, 35,36 our data indicated that alcohol consumption promoted more fatty acid uptake than that in chow diet mice. However, there is no consensus in the literature regarding fatty acid oxidation contributors to hepatic TG levels.…”
Section: Discussionsupporting
confidence: 93%
“…34 Consistently, marked alcohol-induced hepatic lipid/triglyceride accumulation was observed in the EtOH group, indicated by Oil red O staining and elevated liver TC and TG contents. In agreement with previous studies, 35,36 our data indicated that alcohol consumption promoted more fatty acid uptake than that in chow diet mice. However, there is no consensus in the literature regarding fatty acid oxidation contributors to hepatic TG levels.…”
Section: Discussionsupporting
confidence: 93%
“…The identified beneficial structural characteristics to induce serotonin release in Caco-2 cells have similarities to those described for potent TRPA1 activators . In addition, for QGP-1 and Caco-2 cells, a stimulating effect of cinnamaldehyde on serotonin release was demonstrated to depend at least partly on TRPA1 stimulation. , Thus, a potential TRPA1-dependent component for serotonin release in Caco-2 cells was analyzed here as well.…”
Section: Resultsmentioning
confidence: 65%
“…For example, compounds present in ginger, clove oil, mustard oil as well as in cinnamon oil have been shown to be potent ligands for the TRPA1 channel . Only recently, cinnamaldehyde, the main ingredient and key aroma compound of cinnamon oil, has been demonstrated to effectively increase serotonin release and block serotonin reuptake more potently than the other tested cinnamon-derived compounds cinnamic acid, cinnamyl alcohol, and cinnamyl isobutyrate in differentiated Caco-2 cells . The effects of cinnamaldehyde on serotonin release have been demonstrated to be at least partly allocated to the activation of TRPA1 …”
Section: Introductionmentioning
confidence: 99%
“…The HGT-1 cells were starved for one hour with DMEM (2% (w/v) bovine serum albumin (BSA) (Carl Roth)) at standard conditions synchronizing the basal activity [28]. Afterwards, the cells were incubated for six hours with the polar fraction of the grape seed oil (1:5000) diluted in 2-propanol (0.1% final concentration on the cells).…”
Section: Incubation Of Hgt-1 Cells and Cellular Extraction Of Phosphomentioning
confidence: 99%